VAR - Analysis of Global Financial Economic Crisis Impact on Public Budget and Unemployment: Evidence from the Economy of the Kyrgyz Republic - Alymkulova, Nargiza Bakytovna; Atabaev, Nurlan Uzgenovich; Ganiev, Junus Mashrapovich (Economy of Regions, 2016)
The Global financial crisis hit the economy of the Kyrgyz Republic by the third wave of its transmission in the early of 2009. The article examines the impact of the Global financial economic crisis on the public budget and unemployment of the Kyrgyz Republic. We analyzed the transmission of the crisis on the public budget firstly and its effect on unemployment level by using the vector autoregression approach (VAR) and quarterly data for 2005-2013 within the framework of IS-LM model for small open economies with floating exchange rate. There is an inverse relationship between the public budget and remittances inflow, liquidity level, volume of deposits, and exchange rate. As a result of the study, the fall in remittances inflows, liquidity level of the banking system, depreciation of the national currency lead to an increase in public revenue. Therefore, the increase in public spending during the crisis period, with the aim of unemployment reduction, may be considered as a crucial policy. The study result allows to policy-makers to exactly know what channels of transmission mechanism transfer the Global crisis on the public budget and its effect on unemployment level of the republic in order to undertake anticrisis macroeconomic policy. The final result of the study indicates that the increase of unemployment level by 1 % requires the increase of public spending by 0.63 %.